PATHOMORPHOLOGICAL ASPECTS OF PYODERMA GANGRENOSUM - Zapolskiy, M.E.; Lebediuk, M.M.; Svistunov, I.V.; Dudchenko, M.O.; Prokofyeva, N.B.; Bachynska, O.V. (World of Medicine and Biology, 2022)
Pyoderma gangrenosum is a rare inflammatory skin disease of unclear etiology, characterized by neutrophilic infiltration of the dermis with tissue destruction. The pathogenesis of pyoderma gangrenosum has not been fully studied and the variety of clinical forms and difficulties in diagnosing this disease are a major problem for clinicians. Currently, the main diagnostic criterion is histological examination. The aim of our work was to analyze the staging of pathomorphological changes development in patients with pyoderma gangrenosum depending on the dynamics of clinical changes. In 21 histological samples of patients, specific histological markers were identified for each stage and clinical form. The most significant were intravascular fibrin deposition with subsequent development of fibrinoid necrosis, characteristic of earlier stages of the disease, formation of granulomas containing giant cells of foreign bodies characteristic of late necrotic stages of pyoderma gangrenosum. Eosinophilic microabscesses were an important histological feature of the vegetative forms of the disease.
Keywords: gangrenous pyoderma; pathomorphology; histology; diagnosis